Local concentric muscle fatigue of the ankle dorsiflexors and plantar flexors: A reproducibility study - Mattes, K.; Eldin, A. H. W.; Schaffert, N.; Manzer, S. (Isokinetics and Exercise Science, 2015)
Fatigue due to running or local muscle exhaustion is a causative factor for running injuries. Standardized local muscle fatigue can be produced and assessed with isokinetic devices. OBJECTIVE: To examine the absolute and relative reproducibility of local muscle fatigue of the ankle dorsiflexors (DF) and plantar flexors (PF). METHODS: Using a test-retest design, 29 male runners (height: 181.4 ± 4.7 cm, mass: 79.4 ± 9.3 kg, age: 26.6 ± 4.3 years) were twice assessed, isometrically and isokinetically, at 60°/s. Reproducibility was determined by an intraclass correlation coefficient (ICC) and the Bland-Altmann method. RESULTS: For the isometric test, the ICC values ranged from 0.90-0.99, whereas for the isokinetic fatigue protocol and index, they ranged from 0.87-0.97 and 0.76-0.96, respectively. Absolute reproducibility of the PM in the isometric test was 3.1% and 6.4%, for the DF and PF, respectively. The mean of the PM in the isokinetic fatigue protocol was 6.2% and 10.7% and in the fatigue index 12.3% and 21.8%, respectively. CONCLUSION: Using the protocol and instrument described in this paper, local muscle fatigue of the ankle DF and PF may be reproducibly measured.